Flow theory in foreign language learning: from instructional speech to authentic communication - Rakhmonov, Azizkhon Bositkhonovich (The Lingua Spectrum, 2026)
The article explores Csikszentmihalyi’s Flow Theory in the context of foreign language learning. Special attention is given to the concept of flow as a psychological mechanism that ensures a high level of cognitive engagement and facilitates the transition from instructional speech to authentic communicative activity in a second language. Flow is described as a mental state characterized by focused attention, reduced self-monitoring, intrinsic motivation, and the perception of activity as intrinsically rewarding, which plays a crucial role in speech production and the automatization of language skills. The study argues that one of the key conditions for the emergence of flow is the balance between task difficulty and learners’ language proficiency. When communicative tasks exceed learners’ abilities, anxiety and cognitive overload occur; when tasks are too simple, motivation decreases and boredom arises. In contrast, tasks situated in the zone of optimal difficulty promote sustained involvement and spontaneous speech production. From a psycholinguistic perspective, flow is associated with the temporary reduction of metalinguistic control and the activation of procedural memory mechanisms. This leads to decreased reliance on internal translation, reduced interference from the first language, and increased fluency and spontaneity in speech. From a pedagogical viewpoint, flow is interpreted as a strategic goal of modern foreign language education. The article emphasizes the importance of designing learning environments and communicative tasks that foster deep learner engagement, reduce affective barriers, and support the development of communicative competence. Ultimately, flow is viewed not merely as a psychological effect but as a fundamental condition for experiencing language as a natural tool of thought and interaction.